Alterations in the gut microbiota and metabolic profiles coincide with intestinal damage in mice with a bloodborne Candida albicans infection. (May 2021) - Hu, Wanchao; Xu, Dan; Zhou, Ziyang; Zhu, Junfeng; Wang, Dan; Tang, Jianguo
Abstract: Candida albicans is an opportunistic fungus that can threaten life especially in patients with candidemia. The morbidity and mortality of candidemia originating from a central venous catheter (CVC) and illicit intravenous drug use (IVDU) are increasing. However, the mechanism underlying the bloodborne C. albicans infection remains unclear. Herein, we evaluated the gut microbiome, metabolites and intestinal mucosa by constructing the mouse models with candidemia. Model mice were injected with C. albicans via tail vein. Control mice underwent sham procedures. We observed basic life characteristics, intestinal damage-related alterations using hematoxylin and eosin (H&E) staining, intestinal tight junction protein levels, and intestinal permeability in these mice. Fecal samples were analyzed by performing 16S rRNA gene sequencing of the microbiota and LC-MS metabolomics to reveal the perturbations in intestinal flora and metabolism exacerbating intestinal damage. Weight loss, a decreased survival rate, C. albicans infection spread, and colonic epithelial damage occurred in the model group. Furthermore, the intestinal flora abundance was reduced. Several probiotics, such as Lactobacillus, and butyrate-producing bacteria, including Roseburia, Lachnospiraceae, and Clostridia, were depleted, and some pathogenic bacteria, such as Escherichia-Shigella and Proteus, belonging to the Proteobacteria phylum, and the inflammation mediators Ruminococcus and Parabacteroides were enriched in model mice. Multiple differentially altered metabolic pathways were observed and mainly related to bile acid, arachidonic acid, bile secretion, and arachidonic acid metabolism. This study illustrated the effects of a bloodborne C. albicans on the intestinal microbiota, metabolites, and intestinal barrier, which may provide new insights into tests or treatments for candidemia originating from CVC or IVDU. Highlights: Bloodborne C. albicans infection altered the gut microbiota and metabolites. Bloodborne C. albicans infection caused intestinal damage. Perturbations in intestinal flora and metabolism may exacerbate intestinal damage. Altered gut microbiota and metabolites may provide new insights for candidemia.